Increased pain and sensory hyperinnervation of the ligamentum flavum in patients with lumbar spinal stenosis. Issue 3 (28th February 2019) - Benditz, Achim; Sprenger, Svenja; Rauch, Luise; Weber, Markus; Grifka, Joachim; Straub, Rainer H.
ABSTRACT: Nociceptive sensory nerve fibers have never been investigated in the ligamentum flavum (LF) of patients with LSS. The aim was to analyze nociceptive sensory nerve fibers in the ligamentum flavum (LF) of patients with LSS. A prospective study in patients with lumbar spinal stenosis (LSS) undergoing invasive surgical treatment for lumbar spinal stenosis (LSS) with flavectomy was performed. Patients with LSS were subjected to flavectomy and density of sensory and sympathetic nerve fibers, macrophages, vessels, activated fibroblasts, and cells were investigated by immunostaining techniques. A group of patients with acute disc herniation served as control group. We found a higher density of sensory nerve fibers in LSS patients versus controls. These findings support the role of LF in associated low back pain. Density of sensory nerve fibers in LSS, was positively correlated with typical markers of clinical pain and functional disability, but not with LF density of activated fibroblasts. Inflammation as estimated by macrophage infiltration and higher vascularity does not play a marked role in LF in our LSS patients. In the present study, compared to men with LSS, women with LSS demonstrate more pain and depression, and show a higher density of sensory nerve fibers in LF. This study shed new light on nociceptive nerve fibers, which are increased in LSS compared to controls. The findings speak against a strong inflammatory component in LSS. A higher pain levels in women compared to men can be explained by a higher density of nociceptive nerve fibers. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 9999:1–7, 2019.